Lianas and Trees From a Seasonally Dry and a Wet Tropical Forest Did Not Differ in Embolism Resistance but Did Differ in Xylem Anatomical Traits in the Dry Forest - Smith-Martin, Chris M.; Jansen, Steven; Brodribb, Timothy J.; Medina-Vega, José A.; Lucani, Christopher; Huppenberger, Andrea; Powers, Jennifer S. (Frontiers in Forests and Global Change, 2022)
One of the most prominent changes in neotropical forests has been the increase in abundance and size of lianas. Studies suggest that lianas have more acquisitive strategies than trees, which could allow them to take advantage of water more effectively when it is available in water-limited forests, but few studies compared across growth form (i.e., lianas vs. trees) and forest type (i.e., wet vs. seasonally dry). We measured hydraulic and anatomical traits of co-occurring lianas and trees that convey drought resistance (xylem embolism resistance and intervessel pit membranes) and water transport capacity (xylem vessel diameter and density) in a seasonally dry and a wet evergreen tropical forest to address: (1) Are there differences between vulnerability to embolisms (P50—water potential at 50% loss of hydraulic conductivity) and hydraulic safety margins (HSM) across growth form and forest type? (2) How do vessel diameter and density vary across growth form and forest type? (3) Are there differences in xylem intervessel pit membrane thickness across growth form and forest type and does it predict xylem embolism vulnerability in trees and lianas? We examined hydraulic and xylem anatomical traits of 32 species—eight lianas and eight trees in each forest type. We found no difference in P50 and HSMs between lianas and trees and between the wetter and drier forest. Dry forest lianas had 81% greater maximum vessel diameter and 125% greater range in vessel diameter sizes than dry forest trees but, there was no significant difference between life forms in the wet forest. Dry forest species had 50% greater vessel density and 30% greater maximum pit membrane thickness than wet forest ones. Maximum pit membrane thickness was correlated to P50 and HSMs. The main difference between lianas and trees occurred in the dry forest, where lianas had larger maximum xylem vessel size than trees, implying that they have proportionally greater hydraulic conductive capacity than the trees in seasonal forests.